2000
DOI: 10.1046/j.1365-2958.2000.01811.x
|View full text |Cite
|
Sign up to set email alerts
|

Manganese homeostasis in Bacillus subtilis is regulated by MntR, a bifunctional regulator related to the diphtheria toxin repressor family of proteins

Abstract: The Bacillus subtilis yqhN gene encodes a metalloregulatory protein distantly related to the Corynebacterium diphtheriae diphtheria toxin repressor (DtxR). While DtxR mediates the iron‐dependent repression of iron uptake, we demonstrate that yqhN (herein renamed mntR) encodes a manganese modulated regulator of manganese transport. An mntR mutant strain is sensitive to both manganese and cadmium, suggesting that the transport of these metals is derepressed. We selected Tn10 insertions that suppress the Mn(II) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
380
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(403 citation statements)
references
References 65 publications
14
380
3
Order By: Relevance
“…Similar systems have been identified in Bacillus subtilis (Que & Helmann, 2000), Salmonella typhimurium (Kehres et al, 2000) and E. coli (Makui et al, 2000), and confer highaffinity uptake of Mn 2+ . Molecular studies of the enterobacterial (Kehres et al, 2000) and B. subtilis (Que & Helmann, 2000) nramp genes demonstrated that they encode proton-stimulated, highly selective Mn 2+ transporters that play a role in the bacterial response to oxidative stress (Kehres et al, 2000).…”
Section: Introductionmentioning
confidence: 56%
“…Similar systems have been identified in Bacillus subtilis (Que & Helmann, 2000), Salmonella typhimurium (Kehres et al, 2000) and E. coli (Makui et al, 2000), and confer highaffinity uptake of Mn 2+ . Molecular studies of the enterobacterial (Kehres et al, 2000) and B. subtilis (Que & Helmann, 2000) nramp genes demonstrated that they encode proton-stimulated, highly selective Mn 2+ transporters that play a role in the bacterial response to oxidative stress (Kehres et al, 2000).…”
Section: Introductionmentioning
confidence: 56%
“…Growth of an Escherichia coli iron-transport mutant is inhibited in an mntH background, suggesting that manganese may substitute for iron in cells (6). The mntH and sitABCD genes are transcriptionally regulated by iron as well as by manganese in the model organisms E. coli, Salmonella enterica, and Bacillus subtilis (7)(8)(9). However, a regulatory role for manganese in controlling cellular processes other than its own transport is less well understood, and is addressed in the present study.…”
mentioning
confidence: 88%
“…The weaker binding of the mononuclear MntR•Zn 2+ complex to DNA is likely related to a partial loss of restraints between domains, suggesting a mechanism for the selective activation of MntR by Mn 2+ and Cd 2+ over other competing metal ions. [1][2][3]18,20 Ongoing studies will further explore the conformational and structural changes associated with the activation of MntR to its high-affinity DNA-binding state upon metal binding.…”
Section: The Activation Of Mntrmentioning
confidence: 99%
“…1 When cellular levels of manganese are high, MntR represses the transcription of genes encoding manganese uptake transporters by binding to cognate operator sequences. [1][2][3] Manganese is an essential nutrient in bacteria and plays an important role in cellular defense 17,18 MntR is a functional homodimer of 142-residue subunits, each composed of two domains. The 71-residue N-terminal DNA-binding domain consists of three α-helices and two strands of antiparallel β-sheet (Figure 1), the latter forming the flexible "wing" of a winged helix-turn-helix (HTH) motif that interacts with DNA.17 , 19 The Cterminal domain contains four α-helices and forms the dimerization interface with its dyadrelated mate.…”
mentioning
confidence: 99%